Design Application Monitoring The Project Shipbuilding In PT Orela Shipyard - Putra, Rastra Sewa Eka; Sudarmaningtyas, Pantjawati; Setyawan, Henry Bambang (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
PT Orela Shipyard is a company that works in industrial fleet that makes ships according to each project by each different company. When making a ship each company usually enconters schedule delay and to prevent any delays monitoring process is needed to know the progress off the project. Monitoring process of this company is not optimized because it hasn’t fully automated well enough and there isn’t a media that can contain the documents of the ship project. The distance of the main office is far from each ship dock is also a factor that delay the monitoring process of each project. With the problem at monitoring process, so a web based monitoring process application is made to see the progress and documents of the project. The step of making monitoring application uses SDLC method. The result based from the application trials, the application that has been made can solved the problem of the company especially in monitoring process with optimal result and there is no delay in scheduling. This has been tested with the use of black box testing that focused to user input testing on system and the test result show that the application can be used 100%. Kata Kunci : Monitoring, Web, System Development Life Cycle, dan Dashboard.